Sample size calculation for the Andersen‐Gill model comparing rates of recurrent events - Tang, Yongqiang; Fitzpatrick, Ronan (Statistics in medicine, 2019)
Recurrent events arise frequently in biomedical research, where the subject may experience the same type of events more than once. The Andersen‐Gill (AG) model has become increasingly popular in the analysis of recurrent events particularly when the event rate is not constant over time. We propose a procedure for calculating the power and sample size for the robust Wald test from the AG model in superiority, noninferiority, and equivalence clinical trials. Its performance is demonstrated by numerical examples. Sample SAS code is provided in the Supplementary Material.